In search of the Church of St. Alexander: investigation of the Tkon - Poljane site (In situ, 2024)
The paper provides basic information on the excavation of a stone mound at the site of Poljane in Tkon on the island of Pašman, in the area mentioned in the literature as the location of the church of St. Alexander, known from historical sources. Investigation did not establish the presence of a church at that location, however, the remains of a Roman-era/late antique villa rustica were found.
Keywords: the island of Pašman; Tkon; Poljane; Pope St. Alexander I; villa rustica